Common bean varieties demonstrate differential physiological and metabolic responses to the pathogenic fungus Sclerotinia sclerotiorum. (30th March 2018) - Robison, Faith M.; Turner, Marie F.; Jahn, Courtney E.; Schwartz, Howard F.; Prenni, Jessica E.; Brick, Mark A.; Heuberger, Adam L.
Abstract: Plant physiology and metabolism are important components of a plant response to microbial pathogens. Physiological resistance of common bean ( Phaseolus vulgaris L.) to the fungal pathogen Sclerotinia sclerotiorum has been established, but the mechanisms of resistance are largely unknown. Here, the physiological and metabolic responses of bean varieties that differ in physiological resistance to S. sclerotiorum are investigated. Upon infection, the resistant bean variety A195 had a unique physiological response that included reduced photosynthesis and maintaining a higher leaf surface pH during infection. Leaf metabolomics was performed on healthy tissue adjacent to the necrotic lesion at 16, 24, and 48 hr post inoculation, and 144 metabolites were detected that varied between A195 and Sacramento following infection. The metabolites that varied in leaves included amines/amino acids, organic acids, phytoalexins, and ureides. The metabolic pathways associated with resistance included amine metabolism, uriede‐based nitrogen remobilization, antioxidant production, and bean‐specific phytoalexin production. A second experiment was conducted in stems of 13 bean genotypes with varying resistance. Stem resistance was associated with phytoalexin production, but unlike leaf metabolism, lipid changes were associated with susceptibility. Taken together, the data supports a multifaceted, physiometabolic response of common bean to S. sclerotiorum that mediates resistance. Abstract : For common bean, the physiometabolic processes that mediate resistance to the fungal pathogen Sclerotinia sclerotiorum are largely unknown. Here, leaves from resistant and susceptible bean varieties exhibited differential physiological and metabolic responses to S. sclerotiorum infection, including photosynthesis, pH, nitrogen remobilization, and phytoalexin production. The data support that bean resistance involves metabolic changes that alters plant physiology to neutralize S. sclerotiorum pathogenicity mechanisms.